El extraño caso del Dr. Jekyll y Mr. Hyde - Stevenson, Robert Louis, 1850-1894; Díaz Gijón, José R. (José Ramón); Imbert, Ariette; Stevenson, Robert Louis, 1850-1894. (Madrid : Biblioteca Nueva, 2013)
Dr. Jekyll invented a drug that would change him into the ominous Mr. Hyde. His evil nature, however, became the stronger part of him and to his horror, he no longer needed the formula to transform his appearance.
Online resource; title from PDF title page (Digitalia, viewed August 3, 2018)
Keywords: Physicians -- Fiction; London (England) -- Fiction; Multiple personality -- Fiction; Self-experimentation in medicine -- Fiction; Psychological fiction; Horror fiction; Electronic books